دوافع مشاركة المرأة السعودية بأنشطة وقت الفراغ الرياضية وعلاقتها بالسعادة النفسية لدى المترددات على المتنزهات العامة - العنزي، حمود بن محمد ناوي (جامعة أسيوط - كلية التربية الرياضية, 2023)
هدف البحث إلى التعرف على دوافع مشاركة المرأة السعودية بأنشطة وقت الفراغ الرياضية وعلاقتها بالسعادة النفسية لدى المترددات على المتنزهات العامة، والتعرف على الفروق في دوافع المشاركة في أنشطة الفراغ، ومقياس السعادة النفسية وفقاً لمتغيرات (العمر، الممارسة الرياضية، الحالة الاجتماعية). وقد بلغت عينة البحث (۲۳۷) امرأة سعودية، تراوحت أعمارهن ما بين (٢٥ -٥٥ عاماً، وقد تم استخدام مقياس السعادة النفسية لدى ممارسي أوجه نشاط الترويح الرياضي من إعداد "أحمد حلمي قورة، ۲۰۲۲ " والمكون من ٤٥ عبارة تندرج تحت ثلاثة أبعاد رئيسية (تقبل الذات، العلاقات مع الآخرين، الإقبال على الحياة). كما تم بناء مقياس دوافع المشاركة في أنشطة وقت الفراغ مكون ٤٠ عبارة، موزعة على أربعة أبعاد رئيسية (الدوافع الصحية والبدنية، الدوافع المعرفية، الدوافع النفسية، الدوافع الاجتماعية). أشارت النتائج إلى وجود علاقة طردية دالة إحصائياً بين بعض أبعاد دوافع ممارسة أنشطة وقت الفراغ الرياضية وبعض أبعاد مقياس السعادة النفسية، كما أشارت النتائج أنه ليس للعمر تأثير على مقياس الدوافع ومقياس السعادة النفسية، في حين أشارت النتائج أن للدوافع دور في انتظام المرأة السعودية على ممارسة أنشطة وقت الفراغ الرياضية، كما تبين من النتائج أن انتظام المرأة السعودية على ممارسة أنشطة الفراغ الرياضية عند ارتيادها للحدائق والمتنزهات العامة يعد مؤشراً إحصائياً للشعور بالسعادة النفسية. أوصى البحث بضرورة وضع الاستراتيجيات وتصميم الخطط لرفع مستوى الوعي بأهمية ممارسة أنشطة وقت الفراغ الرياضية بغرض تكوين دوافع الممارسة تعزيزا لدورها في رفع مستويات السعادة النفسية للمرأة السعودية. The study aimed to identify the motives for Saudi women’s participation in leisure time sports activities and their relationship to psychological happiness among those who frequent public parks, and to identify the differences in the motives for participation in leisure activities, and the measure of psychological happiness according to the variables (age, sports practice, marital status). The sample of the study was (237) Saudi women, whose ages ranged between (25 - 55) years. The measure of psychological happiness among those practicing aspects of recreational sports activities was used, prepared by “Ahmed Helmy Qora, 2022”, and it consists of 45 statements that fall under three dimensions. Main (self-acceptance, relationships with others, interest in life). A scale of motivations for participating in leisure time activities was also constructed, consisting of 40 statements, distributed over four main dimensions (health and physical motivations, cognitive motivations, psychological motivations, and social motivations). The results indicated that there is a statistically significant direct relationship between some dimensions of the motivations for practicing leisure time sports activities and some dimensions of the psychological happiness scale. The results also indicated that age has no effect on the motivations scale and the psychological happiness scale, while the results indicated that motivations have a role in Saudi women’s regularity in exercising. Leisure sports activities. The results also showed that Saudi women’s regularity in practicing leisure sports activities when they go to gardens and public parks is a statistical indicator of a feeling of psychological happiness. The study recommended the need to develop strategies and design plans to raise the level of awareness of the importance of practicing recreational leisure activities for the purpose of creating motivations for practicing in order to enhance its role in raising the levels of psychological happiness of Saudi women.
Keywords: السعادة النفسية -- المهارات الحياتية -- الأنشطة الثقافية -- الأنشطة الترويحية